The Meanings in the messages: how SMS reminders and real-time adherence monitoring improve antiretroviral therapy adherence in rural Uganda - Ware, Norma C.; Pisarski, Emily E.; Tam, Melanie; Wyatt, Monique A.; Atukunda, Esther cathyln; Musiimenta, Angella; Bangsberg, David R.; Haberer, Jessica E. (AIDS, 2016)
Objective: To understand how a pilot intervention combining SMS reminders with real-time adherence monitoring improved adherence to HIV antiretroviral therapy (ART) for adults initiating treatment in rural Uganda. Design: Qualitative study, conducted with a pilot randomized controlled trial. Methods: Sixty-two pilot intervention study participants took part in qualitative interviews on: preferences for content; frequency and timing of SMS adherence reminders; understandings and experiences of SMS reminders; and understandings and experiences of real-time adherence monitoring. Analysis of interview data was inductive and derived categories describing how participants experienced the intervention, and what it meant to them. Results: SMS reminders prompted taking individual doses of antiretroviral therapy, and helped to develop a ‘habit’ of adherence. Real-time adherence monitoring was experienced as ‘being seen’; participants interpreted ‘being seen’ as an opportunity to demonstrate seriousness of commitment to treatment and ‘taking responsibility’ for adherence. Both SMS reminders and real-time monitoring were interpreted as signs of ‘caring’ by the healthcare system. Feeling ‘cared about’ offset depressed mood and invigorated adherence. Conclusion: Although serving as reminders, SMS messages and real-time adherence monitoring also had larger emotional and moral meanings for participants that they felt improved their adherence. Understanding the larger ‘meanings in the messages,’ as well as their more literal content and function, will be central in delineating how SMS reminders and other adherence interventions using cellular technology work or do not work in varying contexts.
Keywords: Antiretroviral therapy; Mechanisms of effect; Real-time adherence monitoring; SMS